Editorial: Inventing New Perspectives (Al-Jamiah Research Centre, Sunan Kalijaga State Islamic University, 2007)
One impact of globalization is that contemporary issues will rapidly come to fore. In fact, they frequently do not derive from Islamic knowledge or Islamic ethics. They even often do not go with Islamic identities. In sum, such issues will become a challenge for Islamic studies. Due to the challenges, it is notable to pose a question: whether viewpoints having been exercised by scholars in Islamic studies are workable for strong globalization stream or vice versa? Seemingly, if the perspectives do not stand for new global phenomenon, Islamic studies will be marginalized or put aside by both muslims and others. Accordingly, this is because of worldly affairs demand. Given this, efforts leading to the invention of new perspectives are urgent. Scholars will become wiser in facing and handling challenges of the globalization. This come true since they will pose them as inspiration for inventing perspectives called for. This is reasonable due to the fact that they will get an opportunity to explore new perspectives in dealing their subjects. Subsequently, they will be able to make more contribution for social life because of their workable perspective. This seems to be a guarantee to draw attention of a society or community.